Phylogenomics and Spatiotemporal Dynamics of Bovine Leukemia Virus Focusing on Asian Native Cattle: Insights Into the Early Origin and Global Dissemination - Nishikaku, Kohei; Yonezawa, Takahiro; Nishibori, Masahide; Harada, Masashi; Kawaguchi, Fuki; Sasazaki, Shinji; Torii, Yasushi; Imakawa, Kazuhiko; Kawai, Kuniko; Liu, Jianquan; Mannen, Hideyuki; Kobayashi, Tomoko (Frontiers in Microbiology, 2022)
Bovine leukemia virus (BLV), the causative agent of enzootic bovine leukosis, is currently one of the most important pathogens affecting the cattle industry worldwide. Determining where and in which host it originated, and how it dispersed across continents will provide valuable insights into its historical emergence as the cattle pathogen. Various species in the Bos genus were domesticated in Asia, where they also diversified. As native cattle (taurine cattle, zebu cattle, yak, and water buffalo) are indigenous and adapted to local environments, we hypothesized that Asian native cattle could have harbored BLV and, therefore, that they were important for virus emergence, maintenance, and spread. In this study, phylogeographic and ancestral trait analyses—including sequences obtained from Asian native cattle—were used to reconstruct the evolutionary history of BLV. It was shown that, since its probable emergence in Asia, the virus spread to South America and Europe via international trade of live cattle. It was inferred that zebu cattle were the hosts for the early origin of BLV, while taurine cattle played the significant role in the transmission worldwide. In addition, the results of positive selection analysis indicate that yak had a substantially minor role in the transmission of this virus. In this study, endogenous deltaretrovirus sequences in bats, collected in Asian countries, were also analyzed on whether these sequences were present in the bat genome. Endogenous deltaretrovirus sequences were detected from bat species endemic to specific regions and geographically isolated for a long time. Endogenous deltaretrovirus sequences from these geographically isolated species represent ancient exogenous deltaretroviruses distributions. The phylogenetic analysis revealed that these newly obtained endogenous deltaretrovirus sequences were closely related to those of BLV from Asian native cattle, indicating that BLV-related ancient deltaretroviruses circulated in Asia long before the emergence of BLV. Together, our analyses provide evidence for origin and spatiotemporal dynamics of BLV.